Insights into the formation of chiral second sphere coordination complexes with aromatic tris amines: combined single crystal X-ray crystallography and molecular modeling analyses12. Issue 36 (28th September 2015) - Yu, Hong-Cui; Li, Lei; Gao, Ji; Tong, Jian; Zheng, Wenxu; Cametti, Massimo; Famulari, Antonino; Meille, Stefano Valdo; Guo, Fang; Martí-Rujas, Javier
<x xml:space="preserve">Abstract</x> Bulky methyl groups on the central aromatic ring in chiral isostructural second sphere coordination adducts are crucial for the induction of chirality.